Pemanfaatan Big Data Media Sosial Dalam Menganalisa Kemenangan Pilkada - Wulandari, Dewa Ayu Putri; Sudarma, Made; Paramaita, Nyoman (Majalah Ilmiah Teknologi Elektro, 2019)
The  election  of  the  Governor  and  Deputy Governor of  Bali  will  go  through  several  stages  of  elections  starting  from the determination of the Governor and Deputy Governor of Bali to  the  stages  of  vote  counting.    In  the  election  of  the  Governor and  Deputy  Governor  of  Bali  the  community  can  be  directly involved  in the  voting  stage  which  will  be  held  on  June  27,  2018 (General  Commission  Election  or  KPU,  2018).  So  that  it  raises many  opinions,  not  only  positive  and  neutral  opinions  but  also negative  ones.  This  research  is  expected  to  be  able  to  conduct research  on  public  opinion  which  contains  positive,  neutral  and negative    sentiments.    In    this    research    used    tokenization preprocessing   data   N-gram   method.      N-gram   is   a   token consisting  of  three  words  in  each  one  token.  In  the  stemming stages  used  the Nzief  Adriani algorithm.  For  the  classification process  of  this  research  used  the  ‘Naïve  Bays  Classifier  (NBC) method.  In  testing  the  candidate  Governor's  data  the  highest accuracy  was  obtained  from  the  classification  ofKBS-Ace  data on  data  taken  from  twitter  with  89%  accuracy,  91%  precision and   94%   recall   and   lowest   accuracy   when   KBS-Ace   data calcification process on social media Facebook.